RETRACTED ARTICLE: LncRNA HAND2-AS1 exerts anti-oncogenic effects on bladder cancer via restoration of RARB as a sponge of microRNA-146 - Liping Shan; Wei Liu; Yunhong Zhan (Cancer Cell International)
Abstract Background Growing evidence has shown that long noncoding RNA: microRNA: mRNA is implicated in tumor initiation, development, and progression. Long noncoding RNA HAND2-AS1 exhibits anti-cancer effects in diverse cancers. However, the knowledge of HAND-AS1 in bladder cancer development remains unknown. Methods LncRNA and miRNA microarray was conducted to explore different expressed RNA in primary bladder cancer specimens. RNA-RNA interaction prediction tools miRcode ( http://www.mircode.org/ ), DIANA-lncBase v2 ( https://carolina.imis.athena-innovation.gr/diana_tools/web/index.php?r=lncbasev2%2Findex-experimental ), DIANA-TarBase v.8 ( https://carolina.imis.athena-innovation.gr/diana_tools/web/index.php?r=tarbasev8%2Findex ) and miRDB ( http://www.mirdb.org/ ) were employed to predict the interactions between RNA. Bladder cancer cell lines were used to perform cell proliferation and apoptosis assays. Western blot and quantitative Real-time Polymerase Chain Reaction were used to determine the expression of protein and RNA separately. Dual-luciferase assay was conducted to determine the activity of three prime untranslated region of retinoic acid receptor beta (RARB). Furthermore, 5637 human bladder cancer mouse models were established to investigate the interactions of lncRNA: miRNA: mRNA in vivo. Results Based on the RT2 lncRNA PCR Arrays analysis, we validated HAND2-AS1 declined in bladder cancer and negatively correlated with the depth of invasion and grades. The overexpression of HAND2-AS1 in human bladder cancer cells 5637 and RT4 hampered cell proliferation by provoking Caspase 3-triggered cell apoptosis. Besides, one of the HAND2-AS1 sponges, miR-146, elevated in bladder cancer and targeted the tumor suppressor, retinoic acid receptor beta (RARB). We further demonstrated that the HAND2-AS1: miR-146: RARB complex promoted Caspase 3-mediated apoptosis by suppressing COX-2 expression. Finally, the results gained in mouse xenografts suggested that HAND2-AS1 diminished miR-146 expression, thereby reversing the suppression of miR-146 on RARB-mediated apoptosis and contributing to bladder cancer regression. Conclusion The present study sheds light on the fact that lncRNA HAND2-AS1 exerted as a tumor suppressor by releasing RARB from miR-146, leading to tumor proliferation and invasion inhibition. The findings expanded HAND2-AS-mediated regulatory networks' knowledge and provided novel insights to improve the RARB-targeted regimens against bladder cancer.